MENTAL HEALTH ISSUES TOWARDS ANNIE GRAHAM’S BEHAVIOR IN HEREDITARY MOVIE: masalah kesehatan mental terhadap perilaku annie graham dalam film hereditary - christyanty purnama sari (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2023)
This study aims to analyze mental issues suffered by Annie Graham, who is the main character in Hereditary movie. The main character, Annie Graham, a person who has mental issues with Bipolar Disorder, Personality Disorder, Schizophrenia, and PostTraumatic Stress Disorder (PTSD) tries to keep alive despite the fact that her life is extremely challenging and stressful. This study used a qualitative method that involves multiple processes, including watching the movie several times, looking for the standout and intriguing scenes that should be analyzed, and drawing conclusions from the study. The result of the analysis show, (1) there are four types of mental issues that the writer found in this research; Bipolar Disorder, Personality Disorder, Schizophrenia, and Post-Traumatic Stress Disorder. (2) the main character showed five impacts of mental issues such as lying to their partner, strained social relationships, vulnerability genes, prolonged grieving problems, and being faced with a traumatic incident. The outcomes of this study suggest that mental health disorders have an impact on human life. A person's mental issues can transform them into a different person, which can lead to a variety of additional issues such as hallucinations, harming others, and committing violent crimes.